Graphics for urban design. 2nd ed. - Meeda, Bally (ICE Publ., 2018)
Producing a graphical representation of an urban design, town planning or regeneration project is an essential aspect of the design process. How do practitioners use these graphics to best effect and how are created most effectively?Graphics for Urban Design provides guidance on how to use graphic techniques to stimulate and communicate ideas through the urban design process. Now fully updated in this second edition, the book will showcase methods for producing hand-rendered and computer-generated visuals as well as delivering information on drawing maps, collecting data and understanding build perspectives.The book will reveal the whole process and contains chapters that cover- an overview on the history and evolution of urban graphics- characteristics of images- producing drawings- graphics in the urban design process - showing technical expertise - how to produce outputs- managing all aspects of production. Packed with case studies and examples of best practice, this practical, full colour guide will be an must-have purchase for students of graphic design as well as practitioners, commissioners, graphic designers, 3D artists, cartographers and project managers.
Keywords: Städtebau; Stadtplanung; Entwurf; Entwerfen; Darstellung; Stadtgestaltung; Modell; Zeichnung; Kartographie; Rendering; Lehrbuch